DETERMINAÇÃO DE GLICERINA LIVRE EM BIODIESEL UTILIZANDO MÉTODOS DE ANÁLISES ESPECTROFOTOMÉTRICO E CROMATOGRÁFICO/CG-DIC - Louzeiro, Hilton Costa (2007)
This work aim is to analyze the free glycerol content in biodiesel by means of gas chromatography and to establish a spectrophotometer method in the UV Visible region to attain it, as found in the literature. Biodiesel is the result product from the reaction between vegetable oils or animal fat (triglycerides) and alcohols (methanol or ethanol), producing esters fatty acids (biodiesel) and the glycerol as by-product. Even before the purification process, there are traces of free glycerol in the biodiesel. The ANP nº 42 / 2004 Resolution, establishes a maximum allowed limit of 0,02 % (200 mg/L) for free glycerol content per biodiesel mass (B100). The statistical analysis of data showed for the spectrophotometer method, a linear range of 100 to 500 mg/L, with correlation and determination coefficients of 0,9931 and 0,9863; respectively; a mean recovery index of 110,68 % for standard of 100 mg/L and 110,77 % for a standard of 200 mg/L, respectively; accuracy with variation coefficient of 7,94 % for a 200 mg/L standard and sensitivity with detection and quantification limits for the method corresponding to 5,69 mg/L and 18,11 mg/L, respectively. For the chromatographic method the linear range was 50 to 250 mg/L, with correlation and determination coefficients of 0,9964 and 0,9928, respectively; mean recovery index of 100,49 and 89,12 % for standard of 150 and 250 mg/L, respectively; accuracy with variation coefficient of 3,77 % for a 150 mg/L standard and sensitivity with detection and quantification limits for the method of 2,17 and 6,89 mg/L, respectively. Both analytical methods showed to be statistically sensitive and significant for the determination of free glycerin below the limits established by the ANP. However, the chromatographic method presented better adjustment results for the linear model, in agreement with the appraised parameters in the variance analysis.